Is Homeopathic Arnica Effective for Postoperative Recovery? A Meta-analysis of Placebo-Controlled and Active Comparator Trials - Gaertner, Katharina; Baumgartner, Stephan; Walach, Harald (Frontiers in Surgery, 2021)
Background: Homeopathic Arnica montana is used in surgery as prevention or treatment for the reduction of pain and other sequelae of surgery. Our aim was to perform a metaanalysis of clinical trials to assess efficacy of Arnica montana to reduce the inflammatory response after surgery. Method: We conducted a systematic review and metaanalysis, following a predefined protocol, of all studies on the use of homeopathic Arnica montana in surgery. We included all randomized and nonrandomized studies comparing homeopathic Arnica to a placebo or to another active comparator and calculated two quantitative metaanalyses and appropriate sensitivity analyses. We used “Hegde's g,” an effect size estimator which is equivalent to a standardized mean difference corrected for small sample bias. The PROSPERO registration number is CRD42020131300. Results: Twenty-three publications reported on 29 different comparisons. One study had to be excluded because no data could be extracted, leaving 28 comparisons. Eighteen comparisons used placebo, nine comparisons an active control, and in one case Arnica was compared to no treatment. The metaanalysis of the placebo-controlled trials yielded an overall effect size of Hedge's g = 0.18 (95% confidence interval −0.007/0.373; p = 0.059). Active comparator trials yielded a highly heterogeneous significant effect size of g = 0.26. This is mainly due to the large effect size of nonrandomized studies, which converges against zero in the randomized trials. Conclusion: Homeopathic Arnica has a small effect size over and against placebo in preventing excessive hematoma and other sequelae of surgeries. The effect is comparable to that of anti-inflammatory substances.